SERVER PROVIDING A FASHION SERVICE USING A LEARNING MODEL AND AN OPERATING METHOD THEREOF - HAN, KYUNG SIK (2024)
The present invention relates to an operation method of a server, which may include the steps of: obtaining a first image including a user's fashion item; detecting fashion composition information including a fashion category and a fashion design element for an object in the image, and detecting first fashion composition information on the first image based on a learning model providing fashion recommendation information, and obtaining first fashion comment information and first fashion recommendation information corresponding to the first fashion composition information; and transmitting the first fashion comment information and the first fashion recommendation information to an electronic device of the user. 서버의 동작 방법에 있어서, 사용자의 패션 아이템을 포함하는 제1 이미지를 획득하는 단계; 이미지 내의 객체에 대한 패션 카테고리 및 패션 디자인 요소를 포함하는 패션 구성 정보를 검출하고, 패선 추천 정보를 제공하는 학습 모델에 기초하여, 상기 제1 이미지의 제1 패션 구성 정보를 검출하고, 상기 제1 패션 구성 정보에 대응하는 제1 패션 코멘트 정보 및 제1 패션 추천 정보를 획득하는 단계; 및 상기 사용자의 전자 장치로, 상기 제1 패션 코멘트 정보 및 상기 제1 패션 추천 정보를 전송하는 단계를 포함할 수 있다.